The effects of cross-border merger & acquisition and greenfield projects on domestic investment in Latin America - Gondim, Igor Jordano Cassemiro (2019)
This research examines the extent to which outward foreign direct investment (OFDI) from Latin America through greenfield and cross-border merger & acquisition (CBMA) crowds in or crowds out domestic investment (DI). The available literature of relevance on FDI and some recent empirical studies from developing countries suggest that the effects of OFDI on DI is beneficial to home economy. However, the crowding-in effect of OFDI from developing economies does not occur automatically, since it requires firm’s specific mechanisms. Thus, we expand this theoretical framework by disaggregating OFDI into greenfield and CBMA; and providing empirical support to defend the idea that the effects of OFDI on DI are by no means always favorable, but unfavorable depending on the entry mode in foreign markets and firm’s absorptive capacity. Applying panel data analysis and using a data set containing seven countries from Latin America over the 2003–2016 period, the research finds that CBMA crowds out DI and there is no statistically significant effect of greenfield on DI.